Insights into Differences in Response of the USAand the EUROArea to the Recent Crisis - Boris Hosoff; Ivana Sikulova (European Scientific Journal, ESJ, 2017)
The recent financial crisis followed by recession has strongly hit the economies of the USA and euro area. However, their fiscal policy tools available differ significantly, hence also the response of fiscal authorities of both monetary unions to the crisis. On the other hand, in the field of monetary policy, rather similar tools have been used, although with different timing and results so far. The aim of the paper is to underline the main differences and common features of the institutional response to the crisis in the USA and euro area, to compare the developments of selected macroeconomic indicators in the period 2007 – 2015 and formulate conclusions for both monetary unions. The first part of the paper deals with the response of the US Federal Reserve System (Fed) and the European Central Bank (ECB) to the recent crisis. In the second part, the focus is on different possibilities of fiscal policy response in both monetary unions – the USA as a fiscal union and the euro area as a monetary union without a fiscal union. In the third part, developments of selected macroeconomic indicators since the start of the crisis are analysed, namely economic growth, unemployment rate and general government gross debt. The key outcomes are summarized in conclusion.